KEBIJAKAN TURKI TERHADAP SURIAH DALAM MEMERANGI KELOMPOK TERORISME ISIS (ISLAMIC STATE IRAQ and SYRIA) TAHUN 2014 - Ramadhan, Mino; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research purpose is to explins about the policy Turks against the government of syria in the face of terrorist groups ISIS (Islamic State Iraq And Syria), an attack that emanated ISIS in the city Kobani, which is a town located on the border between the Turkish government and the government of Syria, attacks on this border makes Turkey should take development policy measures against Syria This research applying qualitative methods and library research,the Author used security theory of Barry Buzan with the level of the Nation Analysis with realish prespektive. The source of this research are from Of Book, Journals, Publications, Articles,News And Internet. The results of this research indicate that by working together between the government and ethnic Kurdish Syria make Turkey government refused to help Syria in dealing with terrorist groups ISIS because the Turkish government wants to maintain the stability of national security, political and social. Key words: Foreign Policy, National Security,Ethnic Kurds, ISIS